Workload, Time Efficiency, and Fatigue on Miners’ Safety Behavior: A Literature Review - Muhammad Isranul Hakim; Sumaryono Sumaryono (Rifa'Institute, 2026)
Introduction: The mining industry contributes substantially to Indonesia’s economy but exposes workers to high mental demand, time pressure, and prolonged shifts that may compromise safe performance. Previous studies examined workload, the speed–accuracy trade-off, and fatigue in isolation, mostly in manufacturing or laboratory settings, leaving their combined influence on miners’ safety behavior poorly understood. Objective: This research aimed to synthesize existing evidence on how workload, time efficiency, and fatigue relate to the safety behavior of mining workers, and to clarify the gap in the current literature, within a human factors and ergonomics framework. Methods: A narrative literature review was conducted on peer-reviewed articles published between 2016 and 2025, retrieved from major scientific databases; sources were analyzed thematically around four constructs, namely human factors, workload, time efficiency, and fatigue, and their link to safety behavior. Results and Discussion: The literature shows that excessive workload, an unfavorable speed–accuracy trade-off, and accumulated fatigue each reduce accuracy and weaken safety compliance and participation; however, these factors have largely been examined in isolation and outside the mining sector, so their integrated influence on miners’ safety behavior remains unaddressed. Conclusion: Workload, time efficiency, and fatigue jointly shape safety behavior, yet an integrated accuracy model for high-risk mining environments is still a clear gap that future empirical research should address